ANALISIS PENGARUH SUPERVISI TERHADAP KINERJA GURU DI SEKOLAH DASAR BINA MULIA KECAMATAN PONTIANAK TENGGARA - B31110058, Leo Chandra (Jurnal Manajemen Update, 2016)
This research aimed to find out the influence of supervision on the teachers’ performance. The research was carried out the Bina Mulia Elementary School, Sub-district of Southeast Pontianak. This is a descriptive and causal study. The techniques used for data collection were literature study, questionnaires, and observations. The population was all the elementary school teachers of Bina Mulia, Sub-district of Southeast Pontianak with a total of 42 people and 35 of them were the sample. The data analysis was conducted using simple linear regression together with the validity, reliability, normality, linearity tests, and the t-test. The collected data were then processed using SPSS software version 17.0. Based on statistical tests conducted, it was revealed that supervision variable had a significant influence on the performance of the teachers at the Bina Mulia Elementary School, Sub-district of Southeast Pontianak. Keywords: supervision and teachers’ performance